Upaya Peningkatan Kapasitas Soft Power Tiongkok melalui Diplomasi Olahraga dalam Olimpiade Beijing 2008 - Yahya, Immanuela; Sushanti, Sukma; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2025)
This research examines how China sought to enhance its soft power capabilities through sports diplomacy showcased during the 2008 Beijing Olympics. Using a quasi-qualitative model, this study demonstrates how sports themselves serve as a platform for diplomacy and, in this case, were intended to bolster China's soft power capacity. A series of diplomatic efforts were undertaken to alter the world's perception of China as a strong, modern nation capable of aligning with international norms. Using Grix (2019) as a category of soft power, this research focuses on aspects of Culture, Branding and Diplomacy. A series of diplomacy was carried out to change the world's perception of China into a country that is strong, modern, and able to synergize with international relations norms. The research results show that through sports diplomacy, China has succeeded in improving its image in terms of sports culture, its image as a developed and friendly country, and its good diplomatic skills. Overall, China considered succeed in changing foreign audience about its branding to a better light. The research results also reveal that post the 2008 Beijing Olympics, China positioned itself on numerous occasions as a key player in the international arena, and its influence began to be felt in strategic issues on the global stage. Keywords : China, diplomacy, Olympic, sport, soft-power